Impact of left ventricular assist device therapy on the cardiac proteome and metabolome composition in ischemic cardiomyopathy. Issue 3 (10th October 2019) - Shahinian, Jasmin Hasmik; Rog‐Zielinska, Eva A.; Schlimpert, Manuel; Mayer, Bettina; Tholen, Stefan; Kammerer, Bernd; Biniossek, Martin L.; Beyersdorf, Friedhelm; Schilling, Oliver; Siepe, Matthias
Abstract: The changes in the myocardial proteome and metabolome associated with left ventricular assist device (LVAD) therapy in patients with ischemic cardiomyopathy (ICM) are poorly characterized. We investigated the impact of mechanical unloading following LVAD therapy on the myocardial proteome and metabolome. Matched samples of 5 patients' myocardial tissue, harvested at the time of LVAD implant ("pre‐LVAD") or heart transplant ("post‐LVAD"), were studied by quantitative proteomics and metabolomics as well as being probed for T‐tubule structure and connexin‐43 distribution. Moreover, pre‐LVAD proteome profiles of ICM context were bioinformatically compared to pre‐LVAD proteome profiles of dilated cardiac myopathy (DCM). More than 2120 proteins were reliably identified and quantified in paired patient samples. LVAD therapy led to proteomic remodeling, including reduced levels of α‐1‐antichymotrypsin together with an overall decrease of immune response proteins and an increase of proteins involved in membrane biology. Metabolomics highlighted increased glucose and glucose‐6‐phosphate levels in the left ventricle upon LVAD therapy. Wheat germ agglutinin staining demonstrated improved T‐tubule structure. Connexin‐43 displayed a trend for more pronounced intercalated disc localization. In comparing pre‐LVAD proteome profiles of ICM context with pre‐LVAD proteome profiles of dilated cardiac myopathy (DCM), we noticed an overrepresentation in ICM of proteins associated with humoral immune response. Our findings underline an impact of LVAD therapy on left ventricular biology in ICM. The proteomic, metabolomic, and structural alterations described here are typically associated with cardiac recovery. On the molecular level, our findings indicate the possibility of cardiac remodeling under LVAD therapy in ICM.